Nature-Inspired Upward Hanging Evaporator with Photothermal 3D Spacer Fabric for Zero-Liquid-Discharge Desalination - Ye Peng; Yang Shao; Longqing Zheng; Haoxuan Li; Meifang Zhu; Zhigang Chen (Nano-Micro Letters)
Highlights Successful fabrication of photothermal 3D polypyrrole polymerized spacer fabric with excellent water transport capability and high solar absorption efficiency. The upward hanging model evaporator with reverse water feeding achieves an optimized solar evaporation rate of 2.81 kg m−2 h−1 with minimal heat (0.366 W) loss at a 52° tilt. A mangrove leaf-inspired upward hanging model evaporator design separates evaporation and crystallization zones for zero-liquid-discharge desalination.